Stages of change and self-efficacy are related to consumption of food markers among Brazilian adolescents and young adults - Lima, Stefany Corrêa; Melo, Giselle Rhaisa do Amaral e; Schincaglia, Raquel Machado; Souza Lopes, Aline Cristine; Toral, Natacha (Frontiers in Public Health, 2023)
Objective This study aimed at analyzing the association between stages of change, consumption of food markers, and self-efficacy in the adoption of healthy eating practices, adjusted by nutritional knowledge, among Brazilian adolescents and young adults. Methods A cross-sectional analysis was conducted with 347 individuals from schools in the Federal District, Brazil. They completed a self-administered questionnaire covering: consumption of food markers, stage of change, self-efficacy in the adoption of healthy eating practices, and nutritional knowledge. Adjusted logistic regression was conducted. Results Participants in pre-contemplation (OR = 0.22), contemplation (OR = 0.19), decision (OR = 0.13) and action (OR = 0.40) stages have less chance to have healthy eating than those in maintenance, including fruits and vegetables [pre-contemplation (OR = 0.23), contemplation (OR = 0.19), and decision (OR = 0.09)]. Adolescents and young adults in pre-contemplation (OR = 0.29) and contemplation (OR = 0.37) had lower chances of having low consumption of sugar-sweetened beverages compared to those in maintenance (p < 0.05). Adolescents and young adults in pre-contemplation (OR = 0.38) and contemplation (OR = 0.36) were less likely to have high self-efficacy scores than those in maintenance (p < 0.05). Higher score of self-efficacy was associated with a lower chance of having a high consumption of sugar-sweetened beverages (OR = 1.02; p = 0.032). Conclusion Regardless of nutritional knowledge, individuals in the earlier stages of change are less likely to have an adequate consumption of healthy foods markers, including fruits and vegetables, and low sugar-sweetened beverages consumption. They are also less likely to have high self-efficacy scores than those in maintenance. Nutritional interventions to focus on enhancing self-efficacy among adolescents and young adults in earlier stages of change to improve dietary habits.